Designing an assessment tool for teacher leadership competencies in aspiring elementary school principals in Indonesia - Arisa Darwis; Ibrahim Bafadal; Bambang Budi Wiyono; Sultoni; Agung Rinaldy Malik (Sustainable Futures)
This study aims to develop a reliable and valid assessment tool to measure the leadership competencies of prospective elementary school principals in Indonesia, focusing on three key dimensions: Learning Vision, Learning Culture, and Learning Environment. The instrument was developed using Hinkin’s instrument development model, which involves systematic stages of item generation, scale development, and scale evaluation. The instrument was constructed based on theoretical foundations and validated through expert reviews. The development process included empirical testing with a sample of 174 elementary school teachers, ensuring the tool's contextual relevance and alignment with Indonesia's educational priorities. The results of Confirmatory Factor Analysis (CFA) indicated excellent model fit, with indices such as RMSEA (0.035), CFI (0.957), and TLI (0.955) surpassing ideal thresholds. The instrument demonstrated strong internal consistency, with Coefficient ω and α exceeding 0.90 across all dimensions. This tool provides a comprehensive framework for evaluating leadership competencies, addressing contextual challenges, and supporting the selection and professional development of future school leaders in elementary education. Despite its strengths, further refinements are needed to address contextual variability and ensure long-term applicability in Indonesia's diverse educational landscape.